Geothermal dynamic constraints of groundwater source heat pump system in shallow aquifers - Lin, Fei; Ren, Honglei; Wei, Ting; Tao, Yuezan; Li, Yucheng; Yang, Jie (Frontiers in Energy Research, 2023)
Due to the temperature of shallow aquifers being affected by atmospheric temperature, the groundwater source heat pump (GWSHP) is unstable and the operation efficiency of GWSHP is constrained. In the study, the coupling numerical simulation model of the groundwater flow field and temperature field is established based on the continuous monitoring results in an actual experimental site, and the water and thermal migration of shallow aquifer is simulated under the influence of the atmospheric environment. The influence of the dynamic change in ground temperature is analyzed on the GWSHP. The results indicated that the temperature of the shallow aquifer is affected by the external temperature, and the recharge temperature in the summer cooling period was 33 ℃, and that in the winter heating period was 6 ℃ in the actual site, to avoid the occurrence of thermal penetration when there is a gap between the actual situation and the design situation, the single cooler can balance the insufficient cooling capacity in summer under the most unfavorable situation. The research results can also provide a reference for the development and utilization of geothermal energy resources in shallow aquifers.